Koordinasi Mata-Kaki dan Kelincahan terhadap Kemampuan Dribbling Sepakbola - Ibnu Andli Marta; Oktarifaldi Oktarifaldi (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2020)
This study aims to reveal the effect of eye-foot coordination variables and agility on dribbling ability. This research method is a quantitative method using regression analysis. The population in this study were all SSB Balai Baru Padang players. The sampling technique was carried out by proportional random sampling, with a total sample of 32 people. Data were collected using The Arrowhead Agility Test to measure agility, Kick the Ball to the Target to measure eye-leg coordination, and to measure dribbling ability used The Short Dribbling Test. The results of the study and data analysis showed that: (1) Eye-Foot Coordination had a direct and significant effect on dribbling ability, the value of sig = 0.026 <0.05 was obtained. (2) Agility has a direct and significant effect on dribbling ability because the sig = 0.000 <0.05 (3) Eye-Foot Coordination and Agility simultaneously affect dribbling ability with a Sig value of 0.000 <0.05 and Y '= 6,117 + 0,316X1 + 0,562X2. In conclusion, there is a significant influence between eye-foot coordination and agility simultaneously on the dribbling ability of Football School players. Keywords: Eye-Foot Coordination, Agility, Dribbling Ability